Առաջընթացի հայեցակարգը Վիլյամ Գոլդինգի «Արտակարգ դեսպան» վիպակի գեղարվեստական համակարգում - Ռ. Վ. Եղիազարյան (ՀՀ ԳԱԱ հրատ.)
Повесть В. Голдинга «Чрезвычайный посол» можно отнести к жанру исторического романа. Писатель затрагивает одну из самых актуальных проблем современности–проблему прогресса человеческой цивилизации. The present novella by W. Golding can be considered a novel, as it shares many similarities with a parable. In this work, the author looks into the most important problem of our days: the problem of the progress of human civilization.
Keywords: Literature; Language and Literature